Selective Partial Substitution of B‐Site with Phosphorus in Perovskite Electrocatalysts for Highly Efficient Oxygen Evolution Reaction. Issue 3 (19th September 2018) - Zhang, Wenhua; Zhou, Wulan; Zhang, Zhenbao; Chen, Zilong; Tan, Shaozao; Chen, Dengjie
Abstract: Perovskite oxides are promising electrocatalysts for the oxygen evolution reaction (OER). However, the activity and stability of perovskite oxides still needs to be improved to efficiently utilize renewable and clean energy resources. Herein, we selectively introduced phosphorus (P) into SrCo0.8 Fe0.2 O3‐δ (SCF) to form modified perovskite oxides, i. e., SrCo0.8 Fe0.15 P0.05 O3‐δ, SrCo0.75 Fe0.2 P0.05 O3‐δ and Sr(Co0.8 Fe0.2 )0.95 P0.05 O3‐δ . An improved OER activity and stability compared to un‐doped SCF was clearly observed. Meanwhile, the specific surface area, oxygen vacancy content and electronic conductivity increased due to the P doping. Moreover, a lower valence state of B‐site cations induced by the high‐valence P 5+ was detected, which may contribute to the better activity and stability. Among them, the dual‐site substitution to form Sr(Co0.8 Fe0.2 )0.95 P0.05 O3‐δ stands out when evaluating the activity and stability in alkaline solution. The results suggest that the P doping could be an effective strategy to develop perovskite electrocatalysts with high electrocatalytic activity and stability. Abstract : A non‐metal element (i. e. phosphorus) has been successfully substituted in perovskite oxides, and the corresponding electrocatalytic activity and stability are greatly enhanced. Among un‐doped SrCo0.8 Fe0.2 O3‐δ, SrCo0.8 Fe0.15 P0.05 O3‐δ, SrCo0.75 Fe0.2 P0.05 O3‐δ and Sr(Co0.8 Fe0.2 )0.95 P0.05 O3‐δ, the dual‐site substituted Sr(Co0.8 Fe0.2 )0.95 P0.05 O3‐δ stands out when evaluating the activity and stability of the oxygen evolution reaction in alkaline solution. Via mainly affecting B‐site cations, the high‐valence state of phosphorus (P 5+ ) contributes to the improvement of the electrochemical performance.